Pengembangan Sediaan Emulgel Ekstrak Etanol Teh Putih dan Minyak Biji Delima dengan Aktivitas Antioksidan dan Fotoprotektif - Priani, Sani Ega; Syafnir, Livia; Mulkiya, Kiki; Fitrianingsih, Sri Peni; Radina, Faqih (Jurnal Mandala Pharmacon Indonesia, 2024)
White tea and pomegranate seed oil are known to contain many bioactive compounds that make them potentially have antioxidant and photoprotective activities. This study aimed to examine the antioxidant and photoprotective activities of white tea leaf extract and develop it in an emulgel dosage form. White tea is extracted with 70% ethanol at 600C. The extracts were tested for antioxidant activity by the DPPH method and for photoprotective activity by the Mansur method. White tea extract was developed into an emulgel with pomegranate seed oil as the oil phase, stearic acid and TEA as emulsifiers, and viscolam mac 10 as a gelling agent. The results showed that the ethanol extract of white tea had a very strong antioxidant activity with an IC50 value of 10.80 ± 0.75 ppm. White tea ethanol extract also has photoprotective activity with an SPF value of 12.35 ± 0.63, %Te value of 2.13 ± 0.01 %, and %Tp value of 45.13 ± 0.08 % (ultra protection category). White tea extract has been successfully developed into an emulgel preparation with good characteristics and stability in terms of organoleptic, pH, viscosity, spreadability, and rheological behavior. White tea emulgel are stable based on centrifugation and freeze-thaw tests.